OPTIMALISASI PENERAPAN FUNGSI PERENCANAAN (PLANNNING) DALAM MEINGKATKAN EFEKTIVITAS SISWA SMK MAKARYA 1 - Rodiah Nurhasanah; Andi Agustin; Yulio Ananda Saputra; Ahmad Nurhadi (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Planning is one of the fundamental management functions that plays a crucial role in determining the direction, objectives, and strategic steps required to achieve organizational success. In the educational context, the effective implementation of the planning function is essential to improving the quality of learning processes and school activities. This community service program aimed to optimize students' understanding and application of the planning function at SMK Makarya in order to enhance the effectiveness of learning activities, goal setting, time management, and active participation in various school programs. The methods employed in this program included educational counseling, interactive lectures, group discussions, case studies, and evaluations through pre-tests and post-tests administered to participants. The program was conducted directly with vocational high school students as the primary participants. The results indicated a significant improvement in students' understanding of the concept and stages of the planning function, as reflected in their ability to develop systematic activity plans, establish priorities, and identify appropriate strategies for completing academic and organizational tasks. Furthermore, participants demonstrated a high level of enthusiasm throughout the program, as evidenced by their active involvement in discussions and successful completion of the assigned case studies. The optimization of the planning function not only enhanced students' managerial competencies but also contributed to the development of discipline, responsibility, critical thinking, and decision-making skills. Therefore, the continuous implementation of the planning function should be integrated into both classroom learning and extracurricular activities to improve students' effectiveness, productivity, and overall quality of human resources at SMK Makarya.